Precast eco wall with sound insulation - Akmal Hisham, Muhammad Aiman (2022)
As of recent, the idea of a "green campus" has emerged as a topic of discussion due to the fact that educational institutions are regarded as "energy gluttons." This study provides a comprehensive explanation of the meaning of the term "home green campus," as well as an investigation into the functioning system of green campuses and the connotations that are associated with them. The ideas of sustainable development have been discussed at length across a number of stages, and as a direct result of this, it is now widely regarded as a heritage concept among the most influential international institutions. The physical structure of the organisation is considered to be "one of its most significant assets" (HEFCE, 2000,). The land and buildings that belong to educational institutions is typically considered to be their most valuable asset (Abdullah et al. 2012). It is a common observation that the buildings of higher education institutions "are becoming an underutilised asset (Shabha 2004). The first sustainable structure on the UiTM Perak campus is depicted in the figure below.